ABORDAR A INSEGURANÇA ALIMENTAR E NUTRICIONAL DAS FAMÍLIAS ATRAVÉS DE UM CURRÍCULO ESCOLAR ENRIQUECIDO - Botha, Karien; Ferreira, Ronel (Jornal de Políticas Educacionais, 2024)
In recent years, several South African Government policies as well as community-focused interventions have been put into effect in an attempt to address household food and nutrition insecurity. This drive is based on the continued challenge of malnutrition, non-communicable diseases, food and nutrition insecurity, as well as hunger within the country. When considering suitable platforms for such health promotion interventions, schools are regarded as suitable environments and unique resources that can promote quality of life, community-wide health and collective well-being through the implementation of school-based interventions. Against this background, we undertook a participatory research project in three purposefully selected primary schools in a resource-constrained community in South Africa, with the purpose of developing and implementing a school-based intervention with Grade 4 to 6 learners to support healthy food and dietary practices in the community. To be more specific, the Wellness in Lifestyle, Intake, Fitness and Environment (Win-LIFE) intervention aimed to facilitate positive change in terms of healthy food choices, production, preparation and consumption within the participating community. The intervention was conceptualised in collaboration with teachers, school principals, governmental officials, university informants and parents of the participating schools, to be facilitated by teachers as part of the national school curriculum in the subjects Life Skills, and Natural Sciences and Technology. The findings of our study indicate that the Win-LIFE intervention was successful in enriching the national school curriculum. As such, we argue in this article that schools can act as sites for social change in vulnerable communities.